The Use of ChatGPT by History Education Students at the Faculty of Teacher Training and Education, Tadulako University, in Completing Academic Assignments - Nur Ain Ramadhani; Iskandar Iskandar; Idrus Rore; Misnah Misnah (FKIP - Universitas Riau, 2026)
The development of artificial intelligence (AI) has brought significant changes to the world of education, one of which is through the use of ChatGPT as a learning tool for students. This study aims to examine the use of ChatGPT by students in the History Education Program at the Faculty of Teacher Training and Education, Tadulako University, in completing academic assignments, as well as to analyze their perceptions and the impact of its use. The method used was descriptive qualitative research with data collection techniques including observation, interviews, and documentation. The results indicate that students utilize ChatGPT to simplify course material, draft academic assignments such as papers and essays, and identify initial references. Students assessed ChatGPT as having perceived usefulness and perceived ease of use that support the efficient completion of academic tasks. However, its use also leads to negative impacts, including dependency, the risk of plagiarism, and the potential for a decline in critical thinking skills. Thus, ChatGPT serves as a complementary learning tool, not a replacement for primary academic sources. This study concludes that the use of ChatGPT must be balanced with digital literacy and academic ethics so that its positive impacts can be optimized and its negative impacts minimized.